Anti-inflammatory response to acute exercise is related with intensity and physical fitness - Antunes, Barbara Moura [UNESP]; Campos, Eduardo Zapaterra [UNESP]; Thomatieli dos Santos, Ronaldo Vagner; Rosa-Neto, Jose Cesar; Franchini, Emerson; Bishop, Nicolette C.; Lira, Fabio Santos [UNESP] (Wiley-Blackwell, 2019)
Purpose The relationship between inflammatory markers and energetic metabolism has been explored. However, the relationship between exercise intensity and fitness status is unclear, and it is necessary to understand this relationship to apply specific exercise guidance. The purpose of the study was to analyze metabolic and inflammatory responses imposed by acute exercise sessions performed at moderate, heavy, and severe intensities and their relationship with the physical fitness status. Methods Nineteen healthy male volunteers performed three acute exercise sessions until exhaustion or up to 60 minutes on a cycle ergometer at moderate (90% of first ventilatory threshold [VT1]), heavy (midpoint between VT1 and second ventilatory threshold [VT2]), and severe (midpoint between VT2 and maximal aerobic power) intensities. Blood lactate, glucose, NEFA, endotoxin, and cytokines were determined for each exercise session. Peripheral and lipopolysaccharide (LPS)-stimulated release of tumor necrosis factor alpha (TNF-alpha), interleukin (IL)-6, and IL-10 was analyzed before, after, and 60 minutes after sessions. Results In peripheral blood, severe intensity increased lactate, endotoxin, and TNF-alpha immediately after exercise and glucose at 60 min after exercise. There was a trend for IL-10 increase at 60 minutes after exercise in peripheral blood. Immediately after exercise, LPS-stimulated TNF-alpha, IL-6, IL-6/IL-10 ratio, and lactate levels were higher in the severe intensity while nonester fatty acid levels decreased at this time. At 60 minute after exercise, higher concentrations of glucose and a trend for increased IL-10 were observed in severe intensity. A positive correlation was observed between maximal aerobic power and IL-10 (r = 0.513; P = 0.042), and negative correlations between maximal aerobic power and endotoxin (r = -0.531; P = 0.034) and lactate (r = -0.538; P = 0.031) in heavy intensity. Conclusion Our data show a novel finding that higher cytokine responses occur at higher intensities, mainly in severe intensity. However, the anti-inflammatory (IL-10) response was physical fitness-dependent.
Keywords: exercise intensity; health; inflammation; metabolism; physical fitness status